Ontology engineering: reuse and integration. (2nd March 2009) - Toppano, E.; Roberto, V.; Giuffrida, R.; Buora, G.B.
Reuse and integration are major steps in the ontology development process, often unavoidable to lower the costs of a new application. We address the two issues with an engineering approach, and provide a comprehensive account of the state of the art. The domain of e-learning is chosen as a test-bed to verify the feasibility of methods. Reuse and integration are shown to be effective in constructing domain representations with larger coverage and enhanced reasoning capabilities, which significantly extend the expressiveness of semantic software. Problems emerge from the lack of explicit representations of the assumptions taken: when reusing an ontology, one implicitly commits to the underlying context. We conclude that a new methodology should be put forward that views the development as a collaborative work within a community of stakeholders.